Identification and characterization of potential bioactive compounds from the leaves of Leucosidea sericea - Pendota, Srinivasa C; Aremu, Adeyemi O; Slavětínská, Lenka Poštová; Rárová, Lucie; Grúz, Jiří; Doležal, Karel; Van Staden, Johannes (Journal of ethnopharmacology, 2018)
ETHNOPHARMACOLOGICAL RELEVANCE: Leucosidea sericea is a southern African tree used for treating different diseases including microbial infections and inflammatory-related conditions. AIM OF THE STUDY: To isolate and identify the chemicals in Leucosidea sericea which possibly account for the diverse therapeutic effects of the species. MATERIALS AND METHODS: Leaf material was extracted using 20% methanol and subsequently partitioned with different solvents (hexane, dichloromethane, ethyl acetate and butanol). Resultant fractions were subjected to bioactive (antimicrobial)-guided isolation and the structural elucidation was conducted using NMR (1D and 2D) spectroscopic methods. Given the broad uses of Leucosidea sericea in traditional medicine, the extract, fractions and isolated compounds were evaluated in five (5) biological assays in vitro (antimicrobial, antioxidant, acetylcholinesterase (AChE) and anti-inflammatory inhibition as well as cytotoxicity effect). RESULTS: As the most active fractions, from ethyl acetate yielded 5,7-dihydroxychromone (1); 1-hydroxy-2-oxopomolic acid (2); 3,5,7,3´,4´-pentahydroxyflavone (3) and Tiliroside (4). For the first time, these four (4) compounds were isolated from leaves of Leucosidea sericea. These aforementioned compounds demonstrated broad-spectrum antibacterial activity (1.95-125 µg/mL) and noteworthy antifungal (3.9-250 µg/mL) potential. In addition to its noteworthy antimicrobial activity, compound 3 also demonstrated significant antioxidant (EC50 = 14 µg/mL in DPPH assay) and anti-inflammatory (inhibited the level of ELAM by approximately 36% and decreased also the viability of endothelial cells) activities in vitro. Overall, AChE inhibition activity and cytotoxic response was generally weak for the extracts, fractions and isolated compounds. CONCLUSION: The pool of chemicals in Leucosidea sericea were enriched with the isolation and identification of four (4) compounds obtained from the leaf extract. Among these compounds, the significant antimicrobial activity of compound 3 provides strong evidence that support the use of Leucosidea sericea for microbial-related infections in folk medicine.
Keywords: Microbial Sensitivity Tests; Plant Leaves; Medicine, African Traditional; Plant Extracts; Humans; antiflogistika; Antimicrobial; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; lidé; Rosaceae; magnetická rezonanční spektroskopie; Antioxidants; rostlinné extrakty; listy rostlin; antioxidancia; Natural product; Phenolic acids; Anti-inflammatory; Acetylcholinesterase; Anti-Inflammatory Agents; Magnetic Resonance Spectroscopy; tradiční africká medicína; acetylcholinesterasa